Comparative performance of time spectral methods for solving hyperchaotic finance and cryptocurrency systems. (April 2021) - Bambe Moutsinga, Claude Rodrigue; Pindza, Edson; Maré, Eben
Highlights: A comparative performance of Chebyshev spectral methods coupled with domain decomposition in solving hyperchaotic finance systems of differential equations is offered. The proposed methods are fast, robust and offer exponential convergence. A preference is given to spectral integral approach. It is elegant and accurate. Abstract: A comparative performance analysis of two spectral methods on the hyperchaotic finance system (HCFS) and the cryptocurrency pricing problem (CPP) is proposed. The first approach uses a differentiation matrix, the second method considers an integration matrix on a single and multiple domains when the time intervals are large. Numerical simulations are performed against the well established numerical method, Chebfun. It turns out that the spectral method using itegration matrix is more efficient than the other methods on both problems.